Low-threshold room-temperature continuous-wave operation of a terahertz difference-frequency quantum cascade laser source. (18th July 2017) - Fujita, Kazuue; Ito, Akio; Hitaka, Masahiro; Dougakiuchi, Tatsuo; Edamura, Tadataka
Abstract: The performance of a room-temperature continuous-wave (CW) terahertz source based on intracavity difference-frequency generation in a mid-infrared (λ ∼ 6.8 µm) quantum cascade laser with a dual-upper-state active region is reported. The fabricated buried heterostructure device, with a two-section buried distributed feedback grating, operates at two mid-infrared wavelengths and demonstrates a terahertz output of 2.92 THz with a very low threshold current density of 0.89 kA/cm 2 in pulsed operation. Consequently, despite an epitaxial-side-up mounting configuration, the device achieves CW operation at room temperature in which a low CW threshold current density of 1.3 kA/cm 2 is obtained.